Prognostic Value of EEG in Asphyxiated Newborns Treated with Hypothermia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
Researchers at Children's Hospitals in Milan, Italy, determined the prognostic value of electroencephalographic patterns in 23 newborns with severe perinatal hypoxic-ischemic encephalopathy, treated with hypothermia.